Evaluation of thermomechanical fatigue lifetime of BGA lead-free solder joints and impact of isothermal aging. (November 2021) - Roumanille, Pierre; Ben Romdhane, Emna; Pin, Samuel; Nguyen, Patrick; Delétage, Jean-Yves; Guédon-Gracia, Alexandrine; Frémont, Hélène
Abstract: The present work aims at investigating how the BGA solder fatigue life in thermal cycling is affected by prior isothermal aging. The Weibull distributions of SAC305 assemblies are considered through failure analysis and microstructural investigations. The main metallurgical effect of isothermal aging observed on solder joints is a strong coalescence of precipitates. The fatigue life was slightly lowered by an extended aging at 100 °C while exposure at 150 °C proved to increase it. Tin recrystallization and strain-enhanced precipitate coarsening led to intergranular cracking in the solder joints, which was the main failure mode. However, cracking in the PCB laminate was also noticed and mainly present in failed specimens that were previously aged at 150 °C. The prior degradation of the board material near its glass transition temperature and the lower stress in the solder joints due to laminate cracking were proposed to explain the unexpected lifetime extension.